Dream worlds : mass consumption in late nineteenth-century France - Williams, Rosalind H. (University of California Press, 1991)
In Dream Worlds, Rosalind Williams examines the origins and moral implications of consumer society, providing a cultural history of its emergence in late nineteenth-century France.
Keywords: Consumer behavior -- History.; France.; Consommateurs -- Comportement -- Histoire.; HISTORY / Europe / General; Consumer behavior; France; History